1991
DOI: 10.1111/j.1469-8137.1991.tb00029.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of soil disturbance on vesicular—arbuscular mycorrhizal fungi in soils from different vegetation types

Abstract: SUMMARYThe infectivity of vesicular-arbuscular (VA) mycorrhizal fungi m three soils from different vegetation types was compared before and after disturbance. The relative quantities of infective propagules in the disturbed soils were estimated by an infectivity test after the soils were diluted. Spore numbers and mycorrhizal roots were also quantified in each soil.The mycorrhizal colonization of clover roots in tbe infectivity test was not decreased after soil from an annual pasture had been disturbed. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
124
2
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(140 citation statements)
references
References 20 publications
10
124
2
4
Order By: Relevance
“…These data support the suggestion investigation (and unpublished), with the aim of that in undisturbed soil AM are commonly initiated finding a fast method of determining viability of from the hyphal network in soil, as is observed in field-collected spores. Of the stains we examined, sandy soils of Australia (southern WA, (Jasper, only tetrazolium red gave consistent results in Abbott & Robson, 1991);SA, (McGee, 1989); the consecutive experiments, but the results were disHawkesbury plateau, NSW, (Bellgard, 1993); the similar to data from bioassays. In the data we Sydney Basin (G. S. Pattinson & P. A. McGee, presented, the possible reasons for the dissimilarity unpublished)).…”
Section: Survival Of Hyphaesupporting
confidence: 65%
“…These data support the suggestion investigation (and unpublished), with the aim of that in undisturbed soil AM are commonly initiated finding a fast method of determining viability of from the hyphal network in soil, as is observed in field-collected spores. Of the stains we examined, sandy soils of Australia (southern WA, (Jasper, only tetrazolium red gave consistent results in Abbott & Robson, 1991);SA, (McGee, 1989); the consecutive experiments, but the results were disHawkesbury plateau, NSW, (Bellgard, 1993); the similar to data from bioassays. In the data we Sydney Basin (G. S. Pattinson & P. A. McGee, presented, the possible reasons for the dissimilarity unpublished)).…”
Section: Survival Of Hyphaesupporting
confidence: 65%
“…There are many beneficial effects of AMF that could be important in the field, such as increased pathogen protection, salt and heavy metal tolerance, and drought resistance, which I would have been unable to see in this controlled experiment because those stressors were not present (Smith et al 2010) Removal of the mycorrhizal community by sterilization increased the growth of Brachypodium sylvaticum, whereas no growth differences were found with the native grass. Enhanced performance of invasives in soil devoid of biota may facilitate invasion in disturbed sites, where AMF abundance is likely lower than in undisturbed soils (Jasper et al 1991). Interestingly, field studies have shown B. sylvaticum to have lower spore abundance and root AMF colonization than native competitor Elymus glaucus, within identical habitats and consistently between multiple sites in Oregon (Caitlin E. Lee, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Tillage as a morphological species coexist in the same root form of soil disturbance is well known to disrupt system. Strict identification and quantitative meashyphal networks and reduce colonization by arbus-urements of individual species require molecular cular mycorrhizas (Jasper, Abbott & Robson, 1991;probes and biochemical analyses. Molecular approMcGonigle & Miller, 1996).…”
Section: (3) Genotypic Factorsmentioning
confidence: 99%